Exploring health anxiety and its association with quality of life in Yemeni medical undergraduates: A national cross-sectional - Mohamed Terra; Mohamed Baklola; Naji Al-bawah; Husam Addin Ban Rafuid; Ziad Mohammed AL-Othrubi; Hadeel Z. Mohammed; Ehab Sharyan; Mohammed R. Arrabyee; Mohand Almarebi; Akram Arrabyee; Fahd Alsameeai; Sadiq Altbali; et al. (PLoS ONE, 2026)
Background Health anxiety is an increasingly recognized concern among medical students, who are frequently exposed to health-related information and academic stressors. This study aimed to estimate the prevalence of health anxiety among Yemeni medical undergraduates and to examine its association with quality of life (QoL) and selected demographic and academic factors. Methods A national cross-sectional study was conducted between February and April 2025 across ten medical schools in Yemen. A total of 2,573 undergraduate medical students completed an anonymous online questionnaire assessing sociodemographic and academic characteristics, health anxiety using the Short Health Anxiety Inventory (SHAI), self-perceived health, and quality of life using the SF-12 survey. Data were analyzed using descriptive statistics, Pearson’s Chi-square test, the Mann–Whitney U test, Pearson’s correlation, and multivariable logistic regression. Results Clinically significant health anxiety (SHAI ≥27) was observed in 9.8% of participants. Health anxiety was more prevalent among female students and those residing in rural areas (p = 0.010 and p < 0.001, respectively). Lower academic performance, dissatisfaction with academic progress, and personal or family history of psychiatric disorders were significantly associated with health anxiety. Students with clinically significant health anxiety reported lower quality of life scores (median = 27; IQR: 24–29) compared with those without health anxiety (p < 0.001). In multivariable analysis, male gender, urban residence, and academic satisfaction were independently associated with lower odds of health anxiety, whereas low academic performance and psychiatric history were associated with higher odds. A moderate negative correlation was observed between health anxiety and quality of life (r = −0.37, p < 0.001). Conclusion Nearly one in ten Yemeni medical students exhibited clinically significant health anxiety, which was associated with poorer quality of life and unfavorable academic and psychological characteristics. These findings highlight the importance of integrating mental health support and academic counseling services within medical schools to promote student well-being.